ANALYSIS OF THE GREEN LANE IN GAJAH MADA PARK IN MEDAN CITY AS A PUBLIC OPEN SPACE AND DEVELOPMENT EFFORTS A SUSTAINABLE FUTURE - Erliyanti Novarina Halawa; Feby Milanie; Disa Pentaloka Br Sembiring; Cris Yobel Situmorang; Andika Alnas Aldito; Wendista Zebua (PT. Radja Intercontinental Publishing, 2024)
Green lanes are green areas around residential neighborhoods or around cities, which aim to control development growth, prevent two or more cities from merging, and maintain green, recreational, or catchment areas. Smart Green Land is an innovation in the RTH concept that functions as the lung of the city and as a comfortable place through the provision of supporting facilities to create comfort and freshness. This research aims to find out, Studying problems and constraints in the green lane landscape, analyzing problems, developing potential and developing recommendations for sustainable smart green land plans and implementations. Research is carried out on green roads in the city of Medan, and the application of smart Green Land to build a sustainable future. This study uses three stages, namely inventory, data analysis, and data interpretation. The results of the study show that the green lane of Jalan Sei Batang Hari Jalan Gajah Mada and Jalan Sei Batang Panggang are focused on the addition of shrubs, beautiful flowering shrubs, street lighting lamps and seats. Smart Green Land on Jalan Gajah Mada in Medan City and Gajah Mada Park is more focused on adding types of vegetation of flowering plants and grass plants. As well as sports facilities that may be needed in the park as a green open space